Shifting Gears in Pediatric Pyeloplasty: A Systematic Review and Meta-Analysis of Robotic vs Conventional Laparoscopic Approaches for Ureteropelvic Junction Obstruction - Annisa Ulfa Annisa; Gabriel Tandecxi Gabriel; Prayoga Eko Nuryadi Prayoga; Cika Joyita Patria Cika (Frontiers on Healthcare Research, 2026)
Background: Ureteropelvic junction obstruction (UPJO) obstructs the flow of urine and can damage the kidney when it is left untreated. Open pyeloplasty (OP) is still the gold standard, yet laparoscopic pyeloplasty (LP) and robot-assisted laparoscopic pyeloplasty (RALP) achieve comparable success rates. This study aimed to evaluate the efficacy and safety of RALP compared with LP in pediatric patients. Methods: A meta-analysis was conducted on studies published after 2010 that were identified from multiple databases. Comparative studies, including randomized controlled trials (RCTs) and non-RCTs (retrospective cohort and retrospective studies), were included. The primary outcomes were operative success rate, operative time, length of hospital stay, intraoperative blood loss, UPJO recurrence, and complications. The analysis was performed in accordance with the PRISMA guidelines. Results: Sixteen studies (15 cohort studies and 1 RCT) involving 4,707 patients, with an overall moderate risk of bias, were included. RALP significantly increased the success rate by 2% (p = 0.03) and reduced the length of hospital stay by 1.71 days (p < 0.0001) compared with LP. In addition, RALP significantly reduced intraoperative blood loss by 4.63 mL (p = 0.04) and postoperative complications by 42% (p = 0.02). No significant differences were observed in operative time or UPJO recurrence between the two groups. Conclusion: RALP provided significant advantages over LP in pediatric UPJO, particularly in reducing hospital stay, blood loss, and complications, which supports its use as a safe and effective alternative wherever robotic facilities are available.